Endoscopic Resection of Gastric Submucosal Masses by a Dental Floss Traction Method - Chunyan Zeng; Yin Zhu; Xu Shu; Nonghua Lv; Qiang Cai; Youxiang Chen (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. ESE (endoscopic submucosal excavation) is widely used for the treatment of digestive diseases. The dental floss traction (DFT) method has been successfully used to facilitate ESE to resect mucosal lesions such as early gastric cancer. DFT has not been used in ESE to remove submucosal masses. This study aimed to examine the efficacy of DFT-assisted ESE (DFT- ESE) for the removal of submucous masses. Methods. From March 2017 to May 2017, a total of 12 patients with gastric submucosal masses at the First Affiliated Hospital of Nanchang University, Jiangxi, China, were enrolled. The tumor characteristics, en bloc resection rates, complications, and outcomes on follow-up were evaluated for all patients. Results. The 12 submucosal tumors were completely removed by DFT- ESE. Nine were gastrointestinal stromal tumors. Two were Schwannoma, located in the greater curvature of the gastric corpus. One was gastric ectopic pancreas. All the resected tumors were removed completely with intact tumor capsules. There was no more bleeding or perforation after the endoscopic closure of the perforation or the wound after the DFT-ESE, and no recurrences were identified at the time of follow-up. Conclusions. The DFT method efficiently and safely facilitated the ESE procedure during the resection of gastric submucosal tumors. This study was registered with Chinese Clinical Trial Registry under Registration number ChiCTR-OOC-15005833).